ACTION RESEARCH ON MATHEMATICS PHOBIA AMONG SECONDARY SCHOOL STUDENTS - Kaushik Das (Sanata Dharma University Yogyakarta, 2020)
The purpose of this study is to find out the causes of fear in the mathematics of eleventh-grade students and to find a solution. Action research is a method that has proven to be valuable as a problem-solving tool. It can provide opportunities for reflection, improvement, transformation, and solutions to learning. The idea for this project began as a discussion among the Mathematics Phobia at Secondary school in West Bengal followed by WBCHSE Curriculum. The researchers investigate several dimensions of Mathematics Phobia. Several research questions stand out: a) Find out how much is an error in the curriculum? b) Finding students' lack of interest in learning mathematics? c) Find out how students' attitudes toward teaching methods and d) Find out Error in the learning process. The idea for this project began as a discussion among the Mathematics Phobia at Secondary school in West Bengal followed by WBCHSE Curriculum. The researchers selected 50 students from the 11th-grade class, of which 32 were male and 18 are female. Researchers formulated 12 questions and four Hypotheses. The methodology of the study is a mixed type involving interpretative, analytical study of documents, interview, survey questionnaire, observation, qualitative and quantitative data analysis, and study secondary sources, like books, university news, expert opinion, articles, journals, thesis and websites, etc. This study researcher using statistical method percentage bar-graph finally, meaningful suggestions are offered.